Reusable robot system for display and disposal tasks at convenience stores based on a SysML model and RT Middleware. (16th February 2020) - Tsuji, Hiroyasu; Shii, Mayuka; Yokoyama, Shogo; Takamido, Yuki; Murase, Yuji; Masaki, Soshi; Ohara, Kenichi
Abstract : Service robots are increasingly being expected to replace human labor; however, in practical settings, these robots have not been fully utilized, partly because the applications that service robots are expected are quite broad. Suitable hardware and software should be developed in order to cope with a wide variety of applications. Ideally, these resources should be developed using common hardware and software platforms are required. Middleware platforms for robotics software, such as ROS and RT Middleware, have already been developed. However, these platforms still face reusability problems due to the inconsistency present in system architectures. Systems are typically assumed to be reused with a given architecture, and if the user-side software architecture is inconsistent with this assumption, the system's reusability suffers. To address this issue, we propose a procedure for optimizing system development using SysML. In this study, our robot system is designed to complete a display disposal tasks in a convenience store; we verify the validity of the robot system using this task. In addition, to verify the reusability of the developed robot system, we employ system functions developed for another task and demonstrate their reuse and operation. GRAPHICAL ABSTRACT: